Bivalvia Community Structure in The Ecosystem of Jenggalu ‎Mangrove Tourism Park, Bengkulu Province ‎ - Kayla Dwi Hasnatuti; Pariyanto Pariyanto; Mega Sari Apriniarti (ISEJ : Indonesian Science Education Journal, 2026)
Mangrove ecosystems are important habitats for various benthic organisms, including bivalves, which play a role in maintaining the ecological balance of aquatic environments. The Jenggalu Mangrove Forest Tourism Park in Bengkulu City has high potential for biodiversity, but information on the structure of the bivalve community in this area is still limited. This study aims to determine the structure of the bivalve community, including species composition, abundance, and environmental conditions that influence their existence in the Jenggalu mangrove ecosystem. The study was conducted using a survey method with direct sampling techniques at several observation points in the mangrove area. Each bivalve individual found was then identified based on morphological characteristics, counted, and analysed for community structure using ecological indices such as diversity, evenness, and dominance. The results showed that the bivalve community in the Jenggalu mangrove area consisted of several species with different abundance levels at each observation location. The diversity index value was in the moderate category, indicating that environmental conditions were still sufficiently supportive of bivalve life. The relatively stable evenness value indicated a fairly even distribution of individuals between species, while the low dominance value indicated that no species was overly dominant. The results of this study indicate that the mangrove ecosystem in this area still has environmental conditions that are sufficient to support bivalve life. This information is expected to form the basis for efforts to manage and conserve the mangrove ecosystem and preserve the diversity of aquatic biota in the area.